Empowering supervisors with more principles and discretion to implement them will not reduce the dangers of the prudential approach to financial regulation - Tonveronachi, Mario (PSL Quarterly Review, 2010)
The paper addresses two main points: the deficiencies of the past regulatory design and the additional dangers coming from financial reforms that increase the regulatory powers of supervisors. The first point is briefly dealt with reference to past experience and alternative theoretical approaches. For the second point I argue that a prudential regulatory design necessarily leaves large discretionary powers to supervisors, who use them to shape the effective direction impressed to regulation. The current crisis has shown that the force of its first impact much depended on how supervisors had formerly utilised their discretion. Recent reforms and proposals are not changing the basic design of prudential regulation, while give additional regulatory powers to supervisors. If, as a consequence, we will experience in the short-run some regulatory uncertainty, lobbying pressures and international regulatory arbitrage will most probably guide the final result towards few additional regulatory costs and an unchanged systemic fragility. As an alternative we could go back to the methodology, not the specific design, of the Glass-Steagall Act, shaping the financial system by means of structural rules aided by few simple prudential ones. JEL Codes: G18, G20, G28